SUSTAINABLE FINANCIAL MANAGEMENT: STUDY ON COMPANIES THAT IMPLEMENT ESG (ENVIRONMENTAL, SOCIAL, GOVERNANCE) - Windy Permata Suyono; Eka Septariana Puspa (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research aims to analyze the relationship between sustainable financial management and the application of ESG (Environmental, Social, Governance) principles in companies. In the context of global changes that increasingly emphasize sustainability, the integration of ESG in financial management practices is becoming a key factor in creating long-term value and managing business risks. Through a systematic literature review, this research identifies the best practices implemented by companies in integrating ESG into financial planning, investment and risk management. The study results show that companies that actively implement ESG tend to have more stable financial performance, with reduced long-term risk and increased access to cheaper financing. However, the relationship between ESG and financial performance is contextual, influenced by factors such as industry sector, geographic region and company size. The implications of these findings provide guidance for companies to adopt strategic and sustainable ESG policies to support their financial goals. This research also reveals that although ESG offers long-term benefits, implementation challenges, such as initial costs and data limitations, remain major barriers that need to be overcome.